2016
DOI: 10.1007/s10611-016-9671-1
|View full text |Cite
|
Sign up to set email alerts
|

Does local public corruption generate partisan effects on polls?

Abstract: During the recent years of economic boom in Spain, political corruption at the local level boomed as well. In fact, it increased from 7 publicly denounced cases from 1999 to 2003 to at least 180 in the legislative period (2007)(2008)(2009)(2010)(2011). In this paper, we explore this phenomenon in two related ways: how it has affected voting results and political participation, and whether the wrongdoing of local politicians has undermined the voters' trust in them. We constructed a socioeconomic municipality d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…In the case of corruption, most studies have been concerned with estimating its subsequent impact at the ballot box Finan 2008 and2011 for Brazil). The findings are that the impact is limited unless media coverage is broad (Fernández-Vázquez and Rivero 2010; Costas-Pérez et al 2012) and that the impact varies depending on whether the party revealed as being corrupt is on the left or right of the political ideological spectrum (Jiménez and García, 2018). Moreover, local corruption is contagious (González et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of corruption, most studies have been concerned with estimating its subsequent impact at the ballot box Finan 2008 and2011 for Brazil). The findings are that the impact is limited unless media coverage is broad (Fernández-Vázquez and Rivero 2010; Costas-Pérez et al 2012) and that the impact varies depending on whether the party revealed as being corrupt is on the left or right of the political ideological spectrum (Jiménez and García, 2018). Moreover, local corruption is contagious (González et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, Costas‐Pérez, Solé‐Ollé and Sorribas‐Navarro () employ local corruption data in Spain to calculate the effect on electoral outcomes, estimating in a 4% average vote loss after a corruption scandal (14% when corruption scandals are shown in the national press). In a similar fashion, Jiménez and García () analyze corruption effects on abstention as well as proved how corruption provokes the existence of partisan effects. Riera et al () study the patterns of vote punishment of local corruption, and they conclude that the effects of corruption are much more complex than what may seem at first sight.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A new phenomenon, which until then was relatively uncommon –or unreported – in the country, surged during those years: corruption at local level. Before 2000, there was almost no cases reported of local authorities being accused of corruption, but after that date the number has increased exponentially to more than 200 cases during the period 2001–2011 (Jiménez & García, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations